2022
DOI: 10.1186/s12871-022-01583-y
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group is not a predictive factor for the amount of early opioid consumption in postanesthesia care unit: a prospective cohort study in 3,316 patients

Abstract: Background Immediate postoperative pain in the postanesthesia care unit (PACU) is common. Titration of opioid is the most popular strategy for controlling early postoperative pain. ABO blood group has been found to be associated with pain perception. We aimed to find the factors including ABO blood group for predicting the amount of opioid requirement in PACU. Methods This prospective cohort study was performed in 3316 patients who underwent variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Twelve studies (63%) included variables on their DAG with a temporal element. For instance, variables with relevant time dimensions such as ‘preoperative use of gabapentin’ [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies (63%) included variables on their DAG with a temporal element. For instance, variables with relevant time dimensions such as ‘preoperative use of gabapentin’ [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…After this round of full text screening, nineteen studies were included in the final review. Five of these nineteen studies [16,17,[19][20][21] were identified during the updated search in June 2022. References of the final nineteen studies were also screened for relevant studies.…”
Section: Characteristics Of the Final Studies Includedmentioning
confidence: 99%